Effectiveness of Pharmacist‐Led Amiodarone Monitoring Services on Improving Adherence to Amiodarone Monitoring Recommendations: A Systematic Review. Issue 2 (5th February 2016) - Dixon, Dave L.; Dunn, Steven P.; Kelly, Michael S.; McLlarky, Timothy R.; Brown, Roy E.
Abstract : Amiodarone remains the mostly frequently used antiarrhythmic in clinical practice and is most often used to maintain normal sinus rhythm in patients with atrial fibrillation who have failed a rate control strategy. Amiodarone has superior efficacy over other antiarrhythmics, a lower risk of torsade de pointes, and a better cardiovascular safety profile in patients with structural heart disease. However, amiodarone is associated with notable noncardiac toxicities affecting the thyroid, lungs, eyes, liver, and central nervous system. Since 2000, clinicians have been advised to follow amiodarone monitoring guidelines provided by the Heart Rhythm Society. Adherence to these recommendations in clinical practice, however, is suboptimal. Pharmacists play a major role in ensuring the safe and effective use of medications, particularly high‐risk medications such as amiodarone. This qualitative review details the evidence supporting the role of pharmacist‐led amiodarone monitoring services (AMS) in improving adherence to amiodarone monitoring guidelines and identifying adverse effects. Five studies were identified, and, overall, these programs had a favorable impact on improving adherence to guideline‐recommended monitoring standards for amiodarone. The available evidence is limited by the significant variations in study designs and outcome definitions, lack of patient randomization, and limited generalizability. Nevertheless, available studies suggest that pharmacist‐led AMS may improve adherence to recommended monitoring guidelines and identification of amiodarone‐related adverse effects. Further study is warranted to demonstrate whether these services impact the overall quality of care provided to patients receiving amiodarone, which may justify broader implementation.